Transcriptional profiling of colicin-induced cell death of Escherichia coli MG1655 identifies potential mechanisms by which bacteriocins promote bacterial diversity. - Walker, D; Rolfe, M; Thompson, A; Moore, G; James, R; Hinton, J; Kleanthous, K (2004)
We report the transcriptional response of Escherichia coli MG1655 to damage induced by colicins E3 and E9, bacteriocins that kill cells through inactivation of the ribosome and degradation of chromosomal DNA, respectively. Colicin E9 strongly induced the LexA-regulated SOS response, while colicin E3 elicited a broad response that included the induction of cold shock genes, symptomatic of translational arrest. Colicin E3 also increased the transcription of cryptic prophage genes and other laterally acquired mobile elements. The transcriptional responses to both these toxins suggest mechanisms that may promote genetic diversity in E. coli populations, pointing to a more general role for colicins in adaptive bacterial physiology than has hitherto been realized.